Cretevania bechlyi sp. nov., from Cretaceous Burmese amber (Hymenoptera: Evaniidae) - Jennings, John T.; Krogmann, Lars; Mew, Steven L. (Zootaxa, 2013)
The fossil evaniid wasp Cretevania bechlyi sp. nov., is described based on a well preserved female specimen from Creta-ceous Burmese amber. The new species is placed in the genus Cretevania Rasnitsyn, 1975 based on the elongation of the mid and hind trochantellus, the fore wing venation (e.g. first marginal cell triangular and broad, 2m-cu absent, second sub-marginal cell separated from first discal cell), the shape of the petiole (subcylindrical with distal extension) and other dis-tinct morphological features. Cretevania bechlyi sp. nov. differs from all previously described species in having just 10 flagellomeres (11 in other members of the genus) and in the presence of notauli (absent in other species). The new species represents the first species of Cretevania from Burmese amber and significantly expands the known morphological diver-sity of Mesozoic Evaniidae.